Evaluation of solvent effect on the extraction of phenolic compounds and antioxidant capacities from the berries: application of principal component analysis - Boeing, Joana Schuelter; Barizao, Erica Oliveira; Costa e Silva, Beatriz [UNESP]; Montanher, Paula Fernandes; Almeida, Vitor de Cinque; Visentainer, Jesui Vergilio (Biomed Central Ltd, 2014)
Background: This study evaluated the effect of the solvent on the extraction of antioxidant compounds from black mulberry (Morus nigra), blackberry (Rubus ulmifolius) and strawberry (Fragaria x ananassa). Different extracts of each berry were evaluated from the determination of total phenolic content, anthocyanin content and antioxidant capacity, and data were applied to the principal component analysis (PCA) to gain an overview of the effect of the solvent in extraction method.Results: For all the berries analyzed, acetone/water (70/30, v/v) solvent mixture was more efficient solvent in the extracting of phenolic compounds, and methanol/water/acetic acid (70/29.5/0.5, v/v/v) showed the best values for anthocyanin content. Mixtures of ethanol/water (50/50, v/v), acetone water/acetic acid (70/29.5/0.5, v/v/v) and acetone/water (50/50, v/v) presented the highest antioxidant capacities for black mulberries, blackberries and strawberries, respectively.Conclusion: Antioxidants extractions are extremely affected by the solvent combination used. In addition, the obtained extracts with the organic solvent-water mixtures were distinguished from the extracts obtained with pure organic solvents, through the PCA analysis.
Keywords: Solvent extraction; Morus nigra; Rubus ulmifolius; Fragaria x ananassa; Anthocyanins; Multivariate analysis